Effectiveness Between Daily and After-Each-Case Room Disinfection of the Endoscopy Unit - Bo Jin; Yue Hu; Yue Hu; Liang Huang; Xiaoyun Cheng; Jin Zhao; Jin Zhao; Xuejing Yang; Xiling Sun; Tieer Gan; Bin Lu; Bin Lu (Frontiers Media S.A., 2021)
Background: To evaluate the effectiveness between daily and after-each-case room disinfection in the endoscopy unit.Methods: This study was conducted in an endoscopy unit of the First Affiliation of Zhejiang Chinese Medical University. We cultured samples from the surface of endoscopy unit items, including operation unit air, isolation gown of an endoscopist, control panel buttons, workstation mouse, and the bed head of the patient. All the samples were divided into daily and after-each-case room disinfection groups. In addition, each group was subdivided into sedation and nonsedation gastroscopy with and without ventilation room groups.Results: The qualified rate of bed head samples of the patient were lower in the daily room disinfection group (76.67%) compared with the after-each-case group (100%). The isolation gown, mouse at the workstation, and the bed head of the patient demonstrated the lowest bacterial and fungal load in the after-each-case room disinfection group compared with the daily room disinfection group (p < 0.05). In the subgroup analysis, a higher microbial load was observed for the isolation gown of the endoscopist used during nonsedation gastroscopy in an unventilated room under the after-each-case room disinfection pattern (p < 0.05); a higher microbial load was observed for the control panel buttons used during nonsedation gastroscopy under the after-each-case room disinfection pattern (p < 0.05).Conclusions: For risk-free or low-risk patients, daily room disinfection provides the basic health requirements of the endoscopy procedure. However, it is better to adopt the after-each-case room disinfection for the isolation gown of the endoscopist and bed head of the patient. For the patients with high risk, the after-each-case room disinfection is more suitable for every endoscopy unit (www.ClinicalTrials.gov, NCT04399005).